Stagnating economic well-being and unrelenting inequality: Post-2000 trends in the United States - Ajit Zacharias; Thomas Masterson; Fernando Rios-Avila (Levy Economics Institute of Bard College, 2018)
Ajit Zacharias, Thomas Masterson, and Fernando Rios-Avila update the Levy Institute Measure of Economic Well-Being (LIMEW) for US households for the period 2000-13. The LIMEW - which comprises base income, income from wealth, net government expenditures, and the value of household production - is aimed at achieving a more comprehensive understanding of trends in living standards. This policy brief analyzes developments during this period at all levels of the LIMEW distribution, with a particular focus on the significant role played by net government expenditures. The overall trend for 2000 - 13 was one of historic stagnation in the growth of economic well-being for US households, but an examination of the different components of the measure reveals significant shifts taking place behind this headline trend.
Keywords: 330